Does Enhanced Self-Disclosure Really Reduce Social-Religious Ostracism? Evidence From The An Nadzir Congregation - Jalaluddin Basyir; Heddy Shri Ahimsa Putra; Achmad Munjid (Fenomena, 2026)
Until now, for most minority Islamic groups, building coexistence relations with mainstream Islamic groups and the state has not been easy. However, such relations remain possible, as demoNadzired by the An Nadzir congregation. This research investigates the significance of self-disclosure in relation to religious social recognition. Using a qualitative phenomenological approach, data were collected through observations and in-depth interviews with the congregation’s leader and three other informants, then analyzed through data reduction, presentation, and conclusion drawing. This study shows that self-disclosure has become cultural capital for An Nadzir in building its coexistence relations with the mainstream Muslim group and the state, which has led to their gaining religious social recognition to date. It asserts that social ostracism occurs not only because of differences from the majority and the state but also because of self-closure. It contributes to the debate on social recognition between minority Islamic groups and the majority by demonstrating that the negotiation agenda relies not only on macro and meso approaches but also on micro. It is limited to the male perspective of An Nadzir, but necessarily includes the female perspective to avoid gender bias in the negotiation agenda. Hingga saat ini, bagi sebagian besar kelompok Islam minoritas tidak mudah membangun relasi koeksistensi dengan kelompok Islam arus utama dan negara. Namun, konstruksi relasi koeksistensi masih dapat diwujudNadzir, yang dinilai perlu melibatkan pula perspektif perempuan An Nadziruk menyelidiki signifikansi penyingkapan diri terhadap rekognisi sosial keagamaan. Dengan pendekatan kualitatif fenomenologis, data dikumpulkan melalui observasi dan wawancara mendalam dengan pimpinan jemaah dan tiga informan lain, lalu dianalisis melalui reduksi data, penyajian, dan penarikan kesimpulan. Studi ini menunjukkan bahwa penyingkapan diri menjadi modal budaya bagi An Nadzir dalam membangun relasi koeksistensinya dengan kelompok Islam mayoritas dan negara, yang membuat mereka telah memperoleh rekognisi sosial keagamaan sampai sekarang. Studi ini menegaskan bahwa pengucilan sosial terjadi bukan hanya karena berbeda dari mayoritas dan negara, tetapi juga karena menutup diri. Studi ini berkontribusi pada perdebatan mengenai rekognisi sosial antara kelompok Islam minoritas dan kelompok mayoritas dengan menunjukkan bahwa agenda negosiasi tidak hanya mengandalkan pendekatan makro dan meso, tetapi juga mikro. Penelitian ini terbatas pada perspektif laki-laki An Nadzir, yang dinilai perlu melibatkan pula perspektif perempuan An Nadzir guna menghindari bias gender dalam persoalan agenda negosiasi.